Thought Of Socialism According H.O.S.Cokroaminoto - Firdaus Syam; Ali Syafea (Universitas Nasional, 2021)
This paper is entitled Thought of Socialism According to H.O.S Cokroaminoto. Authorinterested in researching and elaborating on his thoughts. Due to the idea of socialismthis appeared in the early era of national awakening. In doing researchThe author uses a qualitative method by analyzing secondary data ISSfrom several books, journals, and existing writings. From the results of these studiesit is known that socialism is a collection of ideas and ideas withinorganize society based on the principle of prioritizing intereststogether in an effort to realize justice and prosperity that is more equitable.H.O.S Cokroaminoto found the compatibility of essence or substancesocialism with moral values in Islamic teachings. According to him there are 2 (two) waysso that the teachings of socialism can be realized. First, by cultivatingawareness of the value of socialism in thoughts and actions in society.Second, by creating a government (gouvernemeny that socialistl).